Evaluation of Kenaf Fibres Reinforced Starch Based Biocomposite Film through Water Absorption and Biodegradation Properties - Ahmad, Zuraida; Razak, Nur Humairah Abdul; Roslan, Nur Suraya Mohd; Mosman, Nazariah (Taylor's University, 2014)
The effect of kenaf short fibres (KF) on thermoplastic sago starch (TPSS) film was investigated for its water absorbency, biodegradability and structure morphology. The TPSS reinforced KF biocomposite film was prepared via casting method at varying TPSS/KF weight percentage of 100/0, 95/05, 90/10, 85/15 and 80/20, while the plasticiser was at a constant amount of 30%, relative to the weight of starch. The result of water absorbency tended to increase for both pure TPSS (100/0) and biocomposite film with prolonged testing days and that the incorporation of KF improves the water resistance of the biocomposite film. Moreover, biocomposite film at 15 wt% of KF content demonstrated the highest weight loss of 39% after 40 days of soil burial for biodegradability test. Scanning Electron Microscopy (SEM) analysed the morphology of the film and revealed good wetting of matrix over the fibres that lead to better adhesion of fibres with the TPSS matrix.